PENGARUH MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) BERBANTUAN VIDEO ANIMAKER TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Nur Azizah, Alifia; Iskandar, Sofyan; Caturiasari, Jennyta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the effect of the Student Teams Achievement Division (STAD) learning model using Animaker video media on the development of critical thinking skills among elementary school students, as well as comparing its effectiveness with the expository method. The underlying issue of this research is the low level of students’ critical thinking skills, which is caused by a lack of innovation in Social Studies (IPS) learning. Using a quantitative approach and a Non-Equivalent Control Group design, the study involved 50 students from two classes—experimental and control—at SDN Bantarjaya 01, Bekasi Regency. Data were collected through pre-tests and post-tests based on Fisher’s critical thinking indicators and analyzed using SPSS. The results showed that the implementation of the STAD learning model supported by Animaker videos significantly improved students' critical thinking skills (p < 0.05). It was more effective and interactive compared to the expository method, contributing to a 61% increase in performance. These findings affirm that learning approaches tailored to students’ characteristics can optimize critical thinking abilities in Social Studies education.